(untitled) (Progressive Agriculture, 2013)
Prey consumption efficiency of the wolf spider, Pardosa pseudoannulata (Boesenberg and Strand) preying on brown planthopper (BPH), Nilaparvata lugens (Stål), green leafhopper (GLH), Nephotettix virescens (Distant) and drosophila, Drosophila melanogaster was investigated in the laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh during the period from June 2008 to April 2009. Depending on the instars and maturity, the spiders were grouped into four different age classes, namely Class I (3rd and 4th instars), Class II (5th and 6th instars), Class III (7th and 8th instars) and Class IV (egg bearing female). When the spiders of each class was supplied with sufficient number of BPH, GLH and Drosophila then the order of the prey consumption of Class I spider was BPH > drosophila > GLH and the order of the prey consumption of Class II, Class III and Class IV were BPH > GLH > drosophila. But in two cases BPH was highly preferred over drosophila and GLH in a mixed diet. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16850 Progress. Agric. 20(1 & 2): 57 62, 2009